﻿Reading levels and attitudes towards reading among Malaysian secondary school students of Esl - Rashidah Rahamat; ﻿Sharifah Nor Puteh; ﻿Parilah Mohd (Universiti Kebangsaan Malaysia, 2010)

(untitled)
﻿Reading is one ofthe most important language skills because it is the foundation of learning. Acquiring the ability to read effectively and eficiently is a great challenge to many English as Second Language (ESL) learners. This study investigated the reading levels of secondary school ESL students and their attitudes towards reading. The assessment instruments included a diagnostic reading test adaptedfrom the Malaysian Ministry of Education and the Mikulecky Behavioral Reading Attitude Measure. A total of 37 Form Four students were selected for the study. The results of the diagnostic tests revealed that 72% (n=27) of the students were at the elementary level. 27% (n=IO) were at the intermediate level, and none of them at the advanced level. Despite oftheir low reading levels, these students showed above average attitudes towards reading. Early diagnosis of students' reading skills is an initial step for teachers to select, arrange, and plan their teaching approaches in reading. Using multidimensional and diverse pedagogies based on students 'interest as well as their abilities may motivate and help students develop a morepositive view towards reading in English. eventually improving their reading.